Aligning urban forest management actions with urban sustainability goals: A multi‐city expert elicitation - Corinne G. Bassett; Susan D. Day; Cecil C. Konijnendijk; Lara A. Roman; Victoria Hemming (Ecosphere)
Abstract City leaders are setting ambitious plans to achieve critical urban sustainability goals such as reducing urban heat, mitigating flooding during storms, and conserving biodiversity, and increasingly rely on urban forests as a key nature‐based solution to such challenges. Current paradigms of urban forest management typically prioritize goals like increasing tree canopy cover that are often viewed as proxies for increased ecosystem service provision, in a general sense. However, urban foresters, the professionals with responsibility to manage urban forests, are increasingly faced with the complex challenge of managing for new goals related to ecosystem services, biodiversity, or people–nature relationships, as cities increasingly set goals centered on such outcomes, without robust guidelines to follow. We ask: How can urban foresters align their street tree management actions with specific urban sustainability goals? We conducted a structured expert elicitation of urban forest professionals in three cities: Vancouver, British Columbia, Canada; Honolulu, Hawaiʻi, United States; and Washington, DC, United States. A socio‐ecological lens was used to examine urban foresters as agents of change in urban ecosystems. Participants assessed the impacts of 40 direct management actions on five goals: (1) canopy cover increase and tree risk reduction, (2) urban heat reduction, (3) people–nature relationships, (4) wildlife habitat, and (5) stormwater interception and infiltration. While certain actions (e.g., in the mature tree maintenance phase) were selected as needed to advance every goal, experts identified numerous actions which aligned with one or several goals, but not all. Preplanting actions, specifically site selection and species selection, presented the greatest opportunities to advance specific goals, suggesting that aligning this phase with city sustainability goals is critical. Participants were highly confident in being able to advance all goals through street tree management, but were more confident in being able to advance the goals of increasing canopy cover while reducing tree risk and of mitigating urban heat, possibly because these goals more closely align with traditional canopy cover goal setting. This research underscores the necessity of considering site‐level ecosystem management actions to advance strategic sustainability goals, while also revealing the complexity of the role and responsibilities of professionals who manage urban ecosystems.